Re Barak. (2016) - Unknown
Abstract : 619 Diplomatic relations — Immunity from jurisdiction — Criminal jurisdiction — Whether serving Israeli Defence Minister and Deputy Prime Minister entitled to immunity — Immunity for members of Special Missions — Customary international law — Convention on Special Missions, 1969, Article 31 State immunity — Immunity from prosecution — Immunity ratione personae — Whether serving Israeli Defence Minister and Deputy Prime Minister entitled to immunity — Reasoning of International Court of Justice in Arrest Warrant Case — Customary international law — The law of England